2021
DOI: 10.1038/s41438-021-00496-0
|View full text |Cite
|
Sign up to set email alerts
|

Methyl jasmonate mediates melatonin-induced cold tolerance of grafted watermelon plants

Abstract: Root–shoot communication has a critical role in plant adaptation to environmental stress. Grafting is widely applied to enhance the abiotic stress tolerance of many horticultural crop species; however, the signal transduction mechanism involved in this tolerance remains unknown. Here, we show that pumpkin- or figleaf gourd rootstock-enhanced cold tolerance of watermelon shoots is accompanied by increases in the accumulation of melatonin, methyl jasmonate (MeJA), and hydrogen peroxide (H2O2). Increased melatoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(81 citation statements)
references
References 49 publications
7
68
0
Order By: Relevance
“…S2). This supported by a previous study that showed the initial H 2 O 2 burst is followed by a burst of melatonin, which further triggers downstream signaling to respond to diverse stress (Gong et al 2017;Li et al 2021). Chemical scavenging of H 2 O 2 partially blocked the induction of seed germination and root growth induced by melatonin or BRs following exposure to cold and drought stress (Figs.…”
Section: Brassinosteroid Biosynthesis and Its Signaling Pathway Are Induced By Melatoninsupporting
confidence: 84%
“…S2). This supported by a previous study that showed the initial H 2 O 2 burst is followed by a burst of melatonin, which further triggers downstream signaling to respond to diverse stress (Gong et al 2017;Li et al 2021). Chemical scavenging of H 2 O 2 partially blocked the induction of seed germination and root growth induced by melatonin or BRs following exposure to cold and drought stress (Figs.…”
Section: Brassinosteroid Biosynthesis and Its Signaling Pathway Are Induced By Melatoninsupporting
confidence: 84%
“…Therefore, flavonol biosynthesis and BR signaling have important functions in plant resistance, and during this process, ROS act as plant signals to respond to environmental changes 48 . In watermelon, the H 2 O 2 content increased and improved adaptation to 4 °C treatment 49 . In our study, the flavonol levels in the McMYB4 -OE lines grown at 28 °C and 18 °C were increased by 493 μg/g and 2715 μg/g, respectively, compared with those in the control treatment, and the BR contents were increased by 14 μg/L and 18 μg/L in these lines, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…Many studies have shown that H 2 O 2 plays an essential signaling role in melatonin-mediated regulation of various physiological processes, including stomatal closure, seed germination, lateral root formation, and response to environmental stimulus [ 19 , 29 , 60 , 61 ]. A recent report revealed that H 2 O 2 mediates melatonin-induced cold tolerance in grafted watermelon plants [ 24 ]. In this study, melatonin induced H 2 O 2 accumulation and ClRBOHD expression in early response (within 6 h) to chilling stress in watermelon ( Figure 1 A).…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the influences of melatonin, H 2 O 2 , or Ca 2+ on watermelon response to cold stress, the seedlings were sprayed with 150 µM melatonin [ 24 ], H 2 O 2 (0.04, 0.2, 1, 5 mM), 20 mM CaCl 2 [ 30 , 31 ], or distilled water (as the control). Melatonin (Sigma-Aldrich, St. Louis, MO, USA) was dissolved in ethanol and then diluted with distilled water at a ratio of 1:10,000 [ethanol:water; v : v ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation